Bibliometric Mapping of Public Trust in the Free Nutritious Meal Program - Irma Cahyani; Iip Permana (YASIN, 2026)
Public trust is essential to the effective evaluation, legitimacy, and continuous improvement of the Free Nutritious Meal Program. Although research on government programs has expanded, bibliometric evidence concerning the position of public trust within the scientific literature on this program remains limited. This study maps the bibliometric landscape, thematic structure, and relative position of public trust in studies related to the Free Nutritious Meal Program published between 2016 and 2026. A descriptive quantitative approach employing bibliometric methods was used. Data were retrieved from Google Scholar through Publish or Perish using the keywords “public trust,” “government program,” “free nutritious meal program,” and “social media.” A total of 995 documents meeting the established inclusion criteria were exported in RIS format and analyzed using VOSviewer through network, overlay, and density visualizations. The findings reveal that the bibliometric network comprised 112 items distributed across eight clusters, interconnected by 1,941 links with a total link strength of 5,520. The dominant keywords were public trust, government, social media, and health, indicating that existing scholarship has primarily examined public trust in relation to governance, digital communication, and public health. By contrast, research specifically addressing public trust in the Free Nutritious Meal Program remains underdeveloped. These findings demonstrate a clear thematic gap and highlight the need for further investigation into the determinants, formation, and consequences of public trust in the program. This study contributes a systematic overview of the field and provides a foundation for future research on government communication, program legitimacy, and public perceptions of nutrition-related social policies.